2023
DOI: 10.1103/physrevb.107.064205
|View full text |Cite
|
Sign up to set email alerts
|

Localization challenges quantum chaos in the finite two-dimensional Anderson model

Abstract: It is believed that the two-dimensional (2D) Anderson model exhibits localization for any nonzero disorder in the thermodynamic limit and it is also well known that the finite-size effects are considerable in the weak disorder limit. Here we numerically study the quantum-chaos to localization transition in the finite 2D Anderson model using standard indicators used in the modern literature such as the level spacing ratio, spectral form factor, variances of observable matrix elements, participation entropy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 106 publications
(192 reference statements)
0
3
0
Order By: Relevance
“…Highly-excited eigenstates of integrable interacting Hamiltonians, such as the spin- 1 2 XXZ chain [19] and the spin- 1 2 Heisenberg (XXX) chain [20], on the other hand have been found to exhibit an average entanglement entropy whose leading volume-law term is not maximal. It is actually close to the one of translationally invariant quadratic models [21][22][23], and of quantum-chaotic quadratic models [24][25][26][27] and typical (Haar-random) Gaussian pure states in the Hilbert space [14,28]. Since the previously mentioned studies of the average eigenstate entanglement entropy of integrable interacting Hamiltonians were carried out in the presence of U(1) [19] and SU (2) [20] symmetry, our goal in this work is to ex-plore what happens in the absence of those symmetries as well as when the model exhibits supersymmetry (in short, SUSY).…”
Section: Introductionmentioning
confidence: 53%
“…Highly-excited eigenstates of integrable interacting Hamiltonians, such as the spin- 1 2 XXZ chain [19] and the spin- 1 2 Heisenberg (XXX) chain [20], on the other hand have been found to exhibit an average entanglement entropy whose leading volume-law term is not maximal. It is actually close to the one of translationally invariant quadratic models [21][22][23], and of quantum-chaotic quadratic models [24][25][26][27] and typical (Haar-random) Gaussian pure states in the Hilbert space [14,28]. Since the previously mentioned studies of the average eigenstate entanglement entropy of integrable interacting Hamiltonians were carried out in the presence of U(1) [19] and SU (2) [20] symmetry, our goal in this work is to ex-plore what happens in the absence of those symmetries as well as when the model exhibits supersymmetry (in short, SUSY).…”
Section: Introductionmentioning
confidence: 53%
“…The point at which the transition occurs, however, is known to drift logarithmically to lower disorder strengths as one increases the system size. In the bottom, right panel, we next plot the gap ratio as a function of ∆ scaled by ln N instead, as discussed in [10], for different system sizes, and see that the graphs intersect at the point (∆ ln N ) * ≈ 15.2. This suggests that in the limit of N → ∞, the transition from GOE to Poisson distributed eigenvalues would occur at ∆ → 0 and the system would, therefore, again localize for arbitrarily small disorder.…”
Section: Frequency Gap Ratiomentioning
confidence: 99%
“…In contrast to thermalizing systems, those in the localized phase do not develop long-range correlations, and subregions retain memory of their initial entanglement structure. Localization is also characterized by unique spectral statistics in measures such as the spectral gap ratio and spectral form factor [6][7][8][9][10], that have interesting connections to random matrix theory as well [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] For example, the dynamical localization (DL) occurring after the Ehrenfest time demonstrates the lack of quantum-classical correspondence in Floquet driven systems due to the quantum coherence, which has received extensive investigations in the past few decades. [23][24][25][26] The mechanism governing chaotic diffusion plays a key role in quantum scrambling and non-equilibrium dynamics. It has been reported that the chaotic dynamics induced by Floquet driven potential dominates the exponentially-fast information scrambling, [27][28][29] the quantum thermalization process [30,31] and entanglement.…”
Section: Introductionmentioning
confidence: 99%